Tax expenditures: spending through the Polish tax system - Dziemianowicz, Ryta; Wyszkowski, Adam; Budlewska, Renata (Economics of the 21st Century, 2014)
The subject of this article is the presentation of tax expenditures as a type of public spending recognized as the off budget expenditures, as well as indicating their influence on Polish budget. This aim was proved in the way of comparative studies of theoretical concepts of tax expenditures and solutions applied in the countries reporting them. Tax expenditures strictly related to particular economic and social policy goals, are special tax provisions which partly or absolutely reduce tax burden of some groups of taxpayers, and in the result – diminish the tax revenue appropriately. The focus on these privileges arisen on the base of tax code is highly important in the current budgetary conditions while the huge part of countries is struggling with imbalances of public finance, and increasing public debts. The overall value of estimated tax expenditures in Poland amounted to 81.6 billion PLN in 2012. Comparing this value to the general government deficit in 2012 of 62.7 billion PLN, the scope of public spending realized out of budget procedure is clearly evident. In 2009-2012 the share of tax expenditures in total public spending amounted on average by 18.3%, and the adequate loss of government revenues was estimated at 26.1% of total tax revenue. Unfortunately this not always transparent part of public spending is out of public control and effectively limits the ability of proper and responsible fiscal policy
Ekonomia XXI Wieku = Economics of the 21st Century, 2014, Nr 4 (4), s. 92-107
Keywords: fiscal imbalance; fiscal policy; Polish tax system; tax expenditures; transparent fiscal policy; nierównowaga fiskalna; polityka fiskalna; polski system podatkowy; transparentna polityka fiskalna